STUDENT TEACHERS’ CONCEPTION OF FEEDBACK WITHIN AN ASSESSMENT FOR LEARNING ENVIRONMENT: LINK TO PUPIL ASPIRATION - Nor Hasnida Che Md Ghazali; Norazilawati Abdullah; Syaza Hazwani Zaini; Mahizer Hamzah (LPMPP Universitas Negeri Yogyakarta, 2020)
Teacher beliefs for conceptualisations of feedback should facilitate pupil development. However, to what extent does the conception of feedback in assessment for learning influence pupil aspirations as commanded by the Malaysian Education Development Plan? Thus, this study is conducted to explore the degree of influence of the conceptions of feedback factors on Pupil Aspiration. A survey research design is used in this study using a self-report inventory on feedback conceptions and pupil aspirations. The participants involved are 490 student teachers who have completed their teaching practical in the government schools in their previous semester. The feedback conception inventory adapted from the Teacher Conceptions of Feedback (TCoF) is used to measure the conception of feedback and the instrument for Pupil Aspiration is developed by the researchers. A structural equation modelling software, the Analysis of Moment Structures was used to test the hypothesized relationship. The analysis involves two-stage approach. Results of the study indicated that the proposed model was supported, and thus revealing that feedback conceptions was associated with Pupil Aspirations. Ten inter-correlated constructs had good psychometric properties. All the nine constructs of feedback conceptions loaded positively on pupil aspirations. The findings will give rise to further hypotheses which could close the gap of the research.